Nonlinear response of functional magnetic resonance imaging - Vinod Venkatraman (2008)
The objective of this research exercise is to analyze and study the nonlinearity present in fMRI response and to propose a nonlinear temporal model for modeling the fMRI response. This is achieved by approximating the fMRI time-series signals obtained from activated regions of subjects performing various experiments, using data-driven neural networks.